Safety First : Perceived Risk of Street Harassment and Educational Choices of Women - Borker, Girija (World Bank, Washington, DC, 2021)
This paper examines the long-term consequences of unsafe public spaces for women. It combines student-level survey data, a mapping of potential travel routes to all the colleges in the choice set, and crowdsourced mobile application safety data from Delhi. The findings show that women choose a college in the bottom half of the quality distribution over a college in the top quintile to feel safer while traveling, relative to men with comparable choice sets who choose a college in the top one-third of the distribution over a college in the top quintile. These findings have implications beyond women’s human capital attainment, such as their participation in the labor force.